Improved storm water management through irrigation rescheduling for city parks. (June 2019) - Nahar, Jannatun; Liu, Su; Liu, Jinfeng; Shah, Sirish L.
Abstract: In this work, a modeling and scheduling approach for an integrated storm water management and irrigation problem is presented. The primary objective is to simultaneously ensure that the green space is irrigated appropriately and the level of the storm water pond is maintained adequately. It is proposed to use closed-loop irrigation scheduling to achieve the objective. A steady-state model is developed to calculate the soil water storage for different irrigation amounts. To handle the uncertainty, real-time feedback from the pond is used to re-evaluate the scheduling optimization problem every week. Simulation results show that the proposed closed-loop scheduling gives much improved control performance.